(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The report will analyze the models and technologies of state identity policy formation in modern “new states”. The report shows effective strategies and institutional practices of identity policy pursued in modern states, designed to ensure the symbolic unity of the citizens of these “new” countries, political stability and political regime stability. The methodological basis of the research is a combination of the principles of constructivism and neoinstitutionalism, since the subjectivity of the state as a political actor in pursuing an identity policy is combined with the need to consolidate its results in specialized formal and informal practices, to create certain political and social institutions. The reported study was funded by RFBR and EISR according to the research project № 19-011-31616 “State Policy in the Field of Formation of Identity: Conceptual Foundations, Technologies and Prospects” in Saint Petersburg State University.